The Functional Outcome of Total Hip Replacement in Patients with Osteonecrosis of the Femoral Head: Study from a Tertiary Care Centre - Lakho, Muhammad Tahir; Khanzada, Muhammad Azfar; Ali, Mumtaz; Memon, Zulfiqar Ali; Ahmed, Bashir; Bhatti, Anisuddin (Pakistan Armed Forces Medical Journal, 2024)
Objective: To assess the functional outcome of total hip replacement in patients with osteonecrosis of the femoral head.Study Design: Prospective, Observational.Place and Duration of Study: Department of Orthopedic surgery, Jinnah Postgraduate Medical Centre, Karachi Pakistan, from Jun to Dec 2019.Methodology: All patients aged 30-60 years of either gender presenting with osteoarthritis of unilateral hip joint were recruited for the study. The functional outcome was assessed at the end of 3 months of surgery. Statistical Package for Social Sciences version 26 was used to perform data analysis.Results: A mean age of the patients was 45.82±9.13 years. Majority of the patients were males, 18(55%) and 22(45%) were females. Mean Body Mass Index of the patients was 26.83±5.26 Kg/m2. There were 31(77.50%) patients with no pain and normal function was found in 15(37.50%) patients. Satisfactory outcome was found in 15(37.50%) patients.Conclusion: The current study reported that the functional outcome was satisfactory in approximately two-fifth of the population with osteonecrosis of the femoral head in our setting.